Pengaruh Dana Pihak Ketiga dan Tingkat Suku Bunga Terhadap Penyaluran Kredit UMKM Pada PT. Bpr Sukawati Pancakanti Periode 2011-2018 - Ni Kadek Juli Artini; A. A. Ketut Jayawarsa; A.A Sri Purnami (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2021)
The purpose of this study is to determine the effect of third party funds and interest rates simultaneously and partially on the distribution of MSME loans. Data analysis techniques used are the classic assumption test, multiple linear regression analysis, F test and t test. Based on the test results from the F test the variable Third Party Funds and Interest Rates significantly influence the number of MSME loans disbursed by PT.BPR Sukawati Pancakanti for the 2011-2018 Period. From the t test on the variable Third Party Funds have a positive and significant impact on the distribution of MSME loans. From the t test the Interest Rate variable has a positive and not significant effect on the distribution of MSME loans channeled by PT. BPR Sukawati Pancakanti for the 2011-2018 period.